Developing a conceptual framework of smart work packaging for constraints management in prefabrication housing production. (October 2019) - Li, Xiao; Shen, Geoffrey Qiping; Wu, Peng; Xue, Fan; Chi, Hung-lin; Li, Clyde Zhengdao
Abstract: Constraints management is the process of satisfying bottlenecks to facilitate tasks assigned to crews being successfully executed. However, managing constraints is inherently challenging in prefabrication housing production (PHP), due to the fragmentation of processes and information during project delivery. Enlightened by the broadly accepted work packaging method and the smart construction objects (SCOs) model, this study aims to define and implement smart work packaging (SWP) for constraints management in PHP. Firstly, the framework of SWP-enabled constraints management (SWP-CM) with three primary functions, including constraints modeling, constraints optimization, and constraints monitoring, is established. In addition, this study develops a layered abstract model as a prototype representation to elaborate on the implementation of SWP for practitioners. Finally, a laboratory-based test is applied to validate the framework. It can prove that SWP indeed opens new avenues for smart constraints management for PHP.